Foucault and animals - Chrulew, Matthew (Human-animal studies ;, 2017)
Foucault and Animals' is the first collection of its kind to explore the relevance of Michel Foucault's thought for the question of the animal. Chrulew and Wadiwel bring together essays from emerging and established scholars that illuminate the place of animals and animality within Foucault's texts, and open up his highly influential range of concepts and methods to different domains of human-animal relations including experimentation, training, zoological gardens, pet-keeping, agriculture, and consumption. Touching on themes such as madness and discourse, power and biopolitics, government and ethics, and sexuality and friendship, the volume takes the fields of Foucault studies and human-animal studies into promising new directions.